Persistence of Bacillus thuringiensis and Bacillus pumilus potential biological control agents of the coffee berry borer under field conditions of Puerto Rico (2022)
Field trials were conducted in two years to evaluate persistence of B. thuringiensis and Bacillus pumilus under field conditions. Strains of B. thuringiensis (3971) and B. pumilus (4185) were isolated from coffee agro-ecosystem in Puerto Rico. Field trials consisted in plots of nine coffee trees arranged in a randomized complete block design, sprayed with Bt-3971 and Bp-4185 at 108, 109, or 1010 colony forming units CFU ml-1 or non-inoculated. In year 1, B. thuringiensis and B. pumilus survived up to six months after inoculation. Monitoring carried out during year 2, re-confirmed the survival of Bt-3971 and Bp-4185 inoculated in coffee trees under field conditions. Overall, Bt-3971 had significantly more recovery rates than Bp-4185. However, the higher bacterial recoveries were 1.24x1013 CFU ml-1 in coffee trees treated with Bt-3971 and 2.48x1013 CFU ml-1 in coffee trees treated with Bp-4185 in year 1 and year 2, respectively, both sprayed with 1010 spores ml-1. B. thuringiensis (3971) and B. pumilus (4185) isolated from coffee fields of Puerto Rico are well adapted to the environmental conditions of the island, and are valuable biological control agents against coffee berry borer.